1984
DOI: 10.3354/meps014259
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal variations in length, dry weight, carbon and nitrogen of Calanus helgolandicus from the Celtic Sea

Abstract: Seasonal fluctuations in mean dry weight of the copepod Calanus helgolandicus were large and contrasted markedly with the small seasonal fluctuations of cephalothorax length. Dry weight was related linearly to cephalothorax length on logarithmic axes by a series of regression equations which were significantly different for each of 8 cruises. Carbon and nitrogen were likewise linearly related to dry weight on logarithmic axes and followed the seasonal fluctuations in dry weight. Dry weight and cephalothorax le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0

Year Published

1984
1984
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(21 citation statements)
references
References 20 publications
0
21
0
Order By: Relevance
“…Our low concentration appears to be close to the limiting food concentrations encountered in the field since our estimates of length and weight correspond to the lower range of the values reported by Bottrell & Robins (1984) on field animals sampled in summer (temperature ~15°C) in the Celtic Sea. Some of the CIV, CV and adults of C. helgolandicus collected off Plymouth at a similar temperature were even smaller and lighter than those from our Cohort L (unpubl.…”
Section: Effects Of the Food Level On The Cohortmentioning
confidence: 66%
“…Our low concentration appears to be close to the limiting food concentrations encountered in the field since our estimates of length and weight correspond to the lower range of the values reported by Bottrell & Robins (1984) on field animals sampled in summer (temperature ~15°C) in the Celtic Sea. Some of the CIV, CV and adults of C. helgolandicus collected off Plymouth at a similar temperature were even smaller and lighter than those from our Cohort L (unpubl.…”
Section: Effects Of the Food Level On The Cohortmentioning
confidence: 66%
“…However, seasonal studies have shown that large weight changes in a species through the year may only be reflected by very small prosome length changes (Bottrell & Robins 1984). Furthermore, relatively large changes in the body weights of individual copepods may accompany only small changes in body length , McKinnon 1996, and statistically significant changes in body carbon, nitrogen and dry weight may not accompany significant changes in prosome length (Thompson et al 1994).…”
Section: Recommendations For New Protocolsmentioning
confidence: 99%
“…However, CIII, CIV, and CV are 3 1, 54, and 64% heavier than predicted by this line, as might be expected for these increasingly lipid-rich stages. Bottrell and Robins (1984) found in C. helgolandicus from the Celtic Sea that dry weight and cephalothorax length showed little or no correlation with food concentration, ingestion rate, population numbers, biomass, or temperature. They did, however, conclude that dry weights of C. paciJicus females (from Vidal 1980a,b), for food concentrations and temperatures in the Celtic Sea, gave predictions that were reasonably good for May through September, but poor for January through March.…”
mentioning
confidence: 90%